PENGEMBANGAN E-MODUL IPA BERBASIS PjBL (Project Based Learning) PADA KELAS VIII UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Suci Ana Yolanda; Yohandri (Postgraduate, University of Mataram, 2025)
Exercise questions used by educators are still in the form of questions that are classified as easy and have not been able to improve the ability to think critically One of the learning needs of learners is a learning resource that is in accordance with the development of the 21st century. (e-module). The purpose of this research is to produce a project-based learning (PjBL)-based science e-module with valid, practical, and effective categories.with valid, practical, and effective categories. This research is a type of research and development with the ADDIE development model, namely Analyze, Design, Development, Implementation, Evaluation. The research instrument consists of a preliminary questionnaire, validation instrument, practicality instrument, and effectiveness instrument. Data analysis techniques consist of preliminary study data, validity data, practicality data, and effectiveness data. Based on the results of the assessment of project-based learning (PjBL) based science e-modules conducted by experts, the results obtained with an average validation by media experts, material experts and linguists are in the valid category. The practicality of e-modules assessed by teachers and students of SMPN 6 Padang Panjang is in the practical and very practical categories. Effectiveness, project-based learning (PjBL) based science e-modules are in the effective category. Based on the results of the study, it can be concluded that project-based learning-based science e-modules meet the criteria of valid, practical, and effective.